Hemodynamic and Morphological Differences Between Unruptured Carotid-Posterior Communicating Artery Bifurcation Aneurysms and Infundibular Dilations of the Posterior Communicating Artery - Yuan, Jinlong; Li, Zhenbao; Jiang, Xiaochun; Lai, Niansheng; Wang, Xuanzhi; Zhao, Xintong; Wu, Degang; Liu, Jiaqiang; Xia, Dayong; Huang, Chenlei; Fang, Xinggen (Frontiers in Neurology, 2020)
Objective: Posterior communicating artery bifurcation aneurysms (PcomA-BAs) and infundibular dilations (PcomA-IDs) are found at the junction between the internal carotid artery (ICA) and the posterior communicating artery (PcomA). Several studies found that PcomA-IDs potentially progress to aneurysms and can even rupture. In our clinical practice, digital subtraction angiography (DSA) helps differentiate PcomA-IDs from unruptured PcomA-BAs. However, when PcomA-IDs are >3 mm in diameter or PcomA are absent on DSA, it is challenging to use DSA to differentiate PcomA-IDs from unruptured PcomA-BAs. Hemodynamic and morphological factors are thought to play important roles in the pathogenesis, progression, and rupture of cerebral aneurysms. We compared hemodynamic and morphological differences in unruptured PcomA-BAs and PcomA-IDs to better manage PcomA-IDs. Methods: We included 83 PcomA-IDs and 115 unruptured PcomA-BAs dignosed and measured using DSA from January 2015 to January 2019. Computational fluid dynamics was performed on these patient-specific models reconstructed using axial slices in DICOM format. Clinical, hemodynamic, and morphological factors were compared between the PcomA-IDs and PcomA-BAs. Significant parameters were analyzed using binary logistic regression analysis to identify independent risk factors. Receiver operating characteristic (ROC) analysis was performed on the independent risk factors to acquire cutoff values. Results: One hemodynamic and four morphyological parameters were significantly different between PcomA-IDs and PcomA-BAs: normalized wall shear stress (NWSS), size, the angle between the ophthalmic segment of the ICA and the PcomA (APcomA), the angle between the ophthalmic and the communicating segment of the ICA (AICA) and the diameter of the PcomA (DPcomA). Binary logistic regression analysis showed that small size and DPcomA as well as APcomA were all independent significant factors characterizing the status of PcomA-IDs and the ROC analysis for independent risk factors indicated the cutoff values of size, APcomA, and DPcomA were 3.45 mm, 66.27°, and 1.24 mm, respectively. Conclusions: Size, DpcomA, and ApcomA could independently characterize the status of PcomA-IDs. These might help us better differentiate them from real aneurysms and guide its management.